Analysis of safety at work in oyster farming in the northeast of Pará (Research, Society and Development, 2022)
This work aimed to identify environmental risks for oyster farmers in the Northeast of Pará, to increase worker safety in the execution of this activity, describing the oyster farming activity, identifying possible physical, biological, environmental and ergonomic risks occurred during the stages of the activity as well as describing the measures preventive measures for worker safety in oyster farming, proposing training and labor gymnastics developed for producers in oyster farming. High rates of health problems and little knowledge about the prevention of these problems were observed. Respondents are not in the habit of performing physical activities before or after the workday to avoid possible back problems. With regard to work safety in oyster farming, the results presented in this research indicate that workers are subject to suffering risks during the practice of the activity, thus needing to adopt measures that will serve as protection for producers. These risks can be contracted through physical agents such as humidity and sun exposure; mechanical related to cuts, falls and projections of particles and biological ones in the case of viruses, bacteria and fungi as well as ergonomic ones in the emergence of repetitive strain injuries or work-related musculoskeletal disorders due to standing or working sitting, monotonous, repetitive and the great physical effort added to the intense workday.